Janda PKI: stigma and sexual violence against communist widows following the 1965–1966 massacres in Indonesia. Issue 128 (2nd January 2016) - Pohlman, Annie
ABSTRACT: This article explores the relationship between the derogatory social constructions and the sexual violence against janda in Indonesia with regard to the experiences of women who were widowed during the 1965 massacres. At that time an estimated 500, 000 people were killed for their alleged ties to the Indonesian Communist Party (PKI). Specifically, it examines how discourses which stigmatise janda as sexually available and/or promiscuous were compounded by the demonisation of women connected with the PKI as dangerous and sexually voracious. By examining the testimonies of women widowed by the death, disappearance or imprisonment of their husbands during the massacres, I argue that janda PKI were subject to two forms of stigmatisation, based on their status as janda and on their connection with the PKI. This was manifest in the sexually predatory behaviours from men in their communities, particularly from the local security forces and militia groups who had taken part in the massacres. By emphasising the political aspects of gender politics which congregate around the extremely derogatory constructions of janda PKI, I articulate how the gendered and sexualised bodies of janda were also politicised and, as a result of the Indonesian military's anti-communist propaganda, made abject in their sexualisation.